Ecotechnological strategies for the reuse of porongo waste using heterogeneous photocatalysis - Pedebos, Maria Eduarda; da Rosa, Gabriel Santos; Druzian, Daniel Moro; da Silva, Maurício Dalla Costa Rodrigues; da Silva, William Leonardo (Disciplinarum Scientia | Naturais e Tecnológicas, 2024)
Waste management is an essential issue in environmental management, as the majority of this waste is not reused or has an incorrect destination. In this way, the porongo (Langenatia siceraria) is a curcubitaceae known in the southern region of Brazil and used culturally to prepare the drink in the state of Rio Grande do Sul. However, during its processing, significant amounts of waste are generated becoming a socio-environmental problem. An alternative for the treatment and adequate disposal of this waste is the production of catalysts using Advanced Oxidative Processes (AOPs), highlighting the heterogeneous photocatalysis. The present work denoted ecotechnological strategies for reusing of residual porongo biomass, highlighting its application in heterogeneous photocatalysis to photodegrade organic pollutants.